Receptor activator of nuclear factor kappa B ligand and osteoprotegerin levels in gingival crevicular fluid - Fatemeh Sarlati; Mandana Sattari; Shilan Razzaghi; Malihe Nasiri (Dental Research Journal, 2012)
Background: Osteoclastogenesis is coordinated by the interaction of three members of the tumor necrosis factor (TNF) superfamily: Osteoprotegerin (OPG)/receptor activator of nuclear factor kappa B ligand (RANKL)/receptor activator of nuclear factor kappa B (RANK). The aim of this study was to investigate RANKL and OPG levels, and their relative ratio in gingival crevicular fluid (GCF) of patients with chronic and aggressive periodontitis, as well as healthy controls. Materials and Methods: In this analytical study, GCF was obtained from healthy (n = 10), mild chronic periodontitis (n = 18), moderate chronic periodontitis (n = 18), severe chronic periodontitis (n = 20), and generalized aggressive periodontitis (n = 20) subjects. RANKL and OPG concentrations were measured by enzyme-linked immunosorbent assay. Statistical tests used were Kruskal-Wallis test, Mann-Whitney U rank sum test, and Spearman′s rank correlation analysis. The level of statistical significance was set at P < 0.05. Results: Mean RANKL concentration showed no statistically significant differences between groups (P = 0.58). There were also no significant differences between mean OPG concentration in the five groups (P = 0.0.56). Moreover, relative RANKL/OPG ratio did not reveal a significant difference between the three study group subjects: healthy, chronic periodontitis (mild, moderate, severe), and aggressive periodontitis (P = 0.41). There was statistically significant correlation between the concentration of sRANKL and Clinical Attachment Level (CAL) in moderate chronic periodontitis patients (R = 0.48, P = 0.04). There was also negative correlation between OPG concentration and CAL in moderate chronic periodontitis patients, although not significant (R = -0.13). Conclusion: RANKL was prominent in periodontitis sites, especially in moderate periodontitis patients, whereas OPG was not detectable in some diseased sites with bleeding on probing, supporting the role of these two molecules in the bone loss developed in this disease.